Propuesta de Mejora del SG- SST de la Escuela Naval de Cadetes Almirante Padilla Cartagena de Indias, según la Resolución 0312 de 2019. (2023)
This proposal to improve the Occupational Health and Safety Management System (SG-SST) for the Almirante Padilla Naval Cadet School in Cartagena de Indias is based on ISO 45001:2018 and Resolution 0312. The main focus of this institution is the training of cadets with the aim of turning them into officers in a period of 5 years. However, the applicability of this proposal extends to the occupational health and safety management system, which currently lacks certification. But the absence of the SG-SST certification of the Naval Academy implies a lack of clarity in the management of plans for the prevention, surveillance and control of risk factors that may arise during the performance of high-risk activities.